Pendampingan Penyusunan Bahan Ajar Sebagai Upaya Peningkatan Efektivitas Pembelajaran TPQ Darul Muttaqien Desa Juwet Kec. Kunjang Kab. Kediri: - - Wildan Habibi; Putri Agustina; Siti Masrukhah; Siti Zuhri Nada (LP3M IAIFA Kediri, 2024)
This research aims to have an impact on increasing the effectiveness of the learning process at the Al-Qur'an Education Park (TPQ) Darul Muttaqien, Juwet Village, Kunjang District, Kediri Regency which is still underdeveloped namely by providing assistance in preparing teaching materials which, with the implementation of the program, implement One method of community service is the Participatory Action Research (PAR). This research begins with problem identification. Next, discuss with the educator. Next, provide assistance in preparing teaching materials which also involves educators, administrators and TPQ students. Next is the implementation of the teaching materials that have been designed and the last is the evaluation of the research work process with the hope that this program can continue and develop optimally. The research results show that mentoring through PAR has succeeded in improving the quality of teaching materials and the effectiveness of learning at TPQ Darul Muttaqien. Educators are more helped by the presence of teaching materials that have been prepared so that the learning process becomes more interactive, shown by the actions of students who are more enthusiastic in understanding the learning material. With this research, it is hoped that in future research the same method can be used in an effort to improve the quality of learning at TPQ and other educational institutions. Keywords: mentoring, teaching materials, learning effectiveness